Diversity, distribution and natural Leishmania infection of sand flies from communities along the Interoceanic Highway in the Southeastern Peruvian Amazon. - Hugo O Valdivia; Victor O Zorrilla; Liz J Espada; Jocelyn G Perez; Hugo R Razuri; Hubert Vera; Roberto Fernandez; Carlos Tong; Bruno M Ghersi; Gissella M Vasquez; Roxanne G Burrus; Andres G Lescano; et al. (Public Library of Science (PLoS), 2021)
The Peruvian-Brazilian border is a highly endemic tegumentary leishmaniasis region in South America. The interoceanic highway is a commercial route that connects Peru and Brazil through Madre de Dios and has raised concerns about its impact on previously undisturbed areas. In order to assess leishmaniasis transmission risk along this highway, we conducted a surveillance study of the sand fly populations in this area. Sand flies were collected between 2009 and 2010 along transects at 200 m, 600 m and 1000 m from six study sites located along the highway (Iberia, La Novia, Alto Libertad, El Carmen, Florida Baja, Mazuko and Mavila) and an undisturbed area (Malinowski). Collected specimens were identified based on morphology and non-engorged females of each species were pooled and screened by kinetoplast PCR to detect natural Leishmania infections. A total of 9,023 specimens were collected belonging to 54 different Lutzomyia species including the first report of Lu. gantieri in Peru. Four species accounted for 50% of all specimens (Lutzomyia carrerai carrerai, Lu. davisi, Lu. shawi and Lu. richardwardi). El Carmen, Alto Libertad, Florida Baja and Malinowski presented higher Shannon diversity indexes (H = 2.36, 2.30, 2.17 and 2.13, respectively) than the most human disturbed sites of Mazuko and La Novia (H = 1.53 and 1.06, respectively). PCR detected 10 positive pools belonging to Lu. carrerai carrerai, Lu. yuilli yuilli, Lu. hirsuta hirsuta, Lu. (Trichophoromyia) spp., and Lu. (Lutzomyia) spp. Positive pools from 1,000 m transects had higher infectivity rates than those from 600 m and 200 m transects (9/169 = 5.3% vs 0/79 = 0% and 1/127 = 0.8%, p = 0.018). El Carmen, accounted for eight out of ten positives whereas one positive was collected in Florida Baja and Mazuko each. Our study has shown differences in sand fly diversity, abundance and species composition across and within sites. Multiple clustered Lutzomyia pools with natural Leishmania infection suggest a complex, diverse and spotty role in leishmaniasis transmission in Madre de Dios, with increased risk farther from the highway.